Evaluating the impact of online discussion boards on student engagement with group work. (30th March 2018) - Delaney, Deborah; Kummer, Tyge‐F.; Singh, Kishore
Abstract: The purpose of this study is to examine the impact of the use of an online discussion board as an assessment item on students learning performance in relation to group work based on Social Learning Theory. The study uses survey questionnaires at the beginning and end of semester together with student grade information. The data analysis consists of (1) a regression analysis to explore the relationship between student interaction and performance and (2) a repeated measures ANOVA to explore changes in attitude and perceived encouragement. Student's perceptions at the outset were found to be important as was the use of the online discussion board as a learning tool even when it is not assessed. Further, students' attitude to the online discussion board improved through the semester however the online assessment task did not encourage domestic students to be more engaged in group‐based activities. In contrast, international students were more encouraged to participate in group‐based activities at the end of the semester. The study has implications for online group activities in education.